1998
DOI: 10.1038/sj.leu.2401074
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloblastic leukemia with minimal myeloid differentiation: phenotypical and ultrastructural characteristics

Abstract: AML-M0 is an infrequent form of acute myeloblastic leukemia characterized by negative reaction with myeloperoxidase (MPO), Sudan Black and lymphoid antigens and positivity for CD13 or CD33. In the present study we describe the immunophenotypical and ultrastructural characteristics of a group of AML-M0 in adult patients. Nine out 218 AML leukemias (4.1%) fulfilled the AML-M0 criteria. CD13 or CD33 were positive in eight out nine cases, with two or more positive myeloid antigens being present in 82% of the cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…35 Conversely, AML with FAB-type M0, the subtype with the least morphologic differentiation, 12 develops preferentially in older patients (Z60 years of age). [36][37][38][39][40][41][42] Historically, but even in the recent WHO classification, 43 immunophenotypically minimally differentiated AML has been considered synonymous with FAB M0. Recent reviews of laboratory findings and proposals for new diagnostic criteria of minimally differentiated AML have focused on better defining AML-M0.…”
Section: Discussionmentioning
confidence: 99%
“…35 Conversely, AML with FAB-type M0, the subtype with the least morphologic differentiation, 12 develops preferentially in older patients (Z60 years of age). [36][37][38][39][40][41][42] Historically, but even in the recent WHO classification, 43 immunophenotypically minimally differentiated AML has been considered synonymous with FAB M0. Recent reviews of laboratory findings and proposals for new diagnostic criteria of minimally differentiated AML have focused on better defining AML-M0.…”
Section: Discussionmentioning
confidence: 99%
“…27 The positivity of leukemic cells for CD34, a marker of hematopoietic stem cells, is common in AML-M0, M1 or M7, and rarely seen in AML-M2 to M5. 8,28,29 The high percentage of CD34 + leukemic precursors in the AML-M0 leukemia model allowed us to test their differential immune recognition in comparison with more differentiated blasts.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some authors reported that AML M0 is significantly associated with the coexpression of lymphoidassociated markers (ie CD4 or CD7). 6,7 The incidence of CD5-positive AML is 3% in children and 4% in adults and is distributed similarly through all FAB types. 5,7 The coexpression of lymphoidassociated markers does not seem to be associated with an adverse overall survival in these patients.…”
Section: Case Reportmentioning
confidence: 99%